If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -6x) = -100 (4 * 2 + -6x * 2) = -100 (8 + -12x) = -100 Solving 8 + -12x = -100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -12x = -100 + -8 Combine like terms: 8 + -8 = 0 0 + -12x = -100 + -8 -12x = -100 + -8 Combine like terms: -100 + -8 = -108 -12x = -108 Divide each side by '-12'. x = 9 Simplifying x = 9
| 9x-3=3(2x-8) | | 2x^2-8x+3=y | | 2y+4x=-x^2-y^2+4 | | x+4x-2+6x-5=180 | | 6x-4=2[4+2x] | | 6x+7=-x-21 | | 52b^2-156b-407=0 | | z+10=23 | | 9+5x=7x-5 | | 2x-7=1+x | | 6x-5+4x-2+x=180 | | x^3-165x+350=0 | | -4x+9=-15+4x | | 2x^2-.75=0 | | g(x)=x^2(1-8x) | | X+(-1.87)x=1.4967 | | v-(-65)=50 | | 12y^3-2y^2+15y=0 | | (-3-2I)+(-5-3I)= | | X+(-1.87)x= | | 225=4x*9 | | 2x+23=3x-3 | | 9x+7+8x+3=95 | | 5y-10y+4x=12x | | hx+p=nx+v | | 2y+7=y-8 | | 18*0.04= | | (2+6I)(2-5I)= | | -3(t-6)-(t+2)=2 | | 4x^2+3y^2+8x-6y-5=0 | | A=a+(n-7)d | | 2y-7=y+8 |